The Prohibition of Child Slavery in South Africa, Uganda and Zimbabwe: Overcoming the Challenges of Implementation of Legislation - Mavunga, Rufaro (Comparative and International Law Journal of Southern Africa, 2020)
The elimination of child slavery is a priority in many international instruments today. This article investigates the extent to which South Africa, Uganda and Zimbabwe comply with international instruments to which they are party. It therefore compares and contrasts the different legislative provisions that prohibit child slavery in South Africa, Uganda and Zimbabwe. The municipal laws of these countries in some cases do not always reflect the principles and standards of international law. The research subsequently prompts the reformulation or refinement of some laws. In other instances, legislation adequately prohibits child slavery, but the law is ineffectively enforced. These states face challenges with the enforcement of legislation and this article further investigates some of the problems faced with regard to the implementation. Furthermore, this article also proposes practical ways in which states can effectively overcome the challenges they face in enforcing such laws.